From Domestic to Public: A Bell Hooks’ Intersectional Analysis of Feminism Representation in Abdi Mangungkung Dance - Wigaringtyas, Silih (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This research examines the representation of feminism in the Abdi Mangungkung dance through the lens of bell hooks' feminist theory. While traditional dance often relegates women to symbolic or aesthetic roles, there remains a research gap concerning how historical Javanese narratives can be reinterpreted as sites of political empowerment. The primary purpose of this study is to explore the transition of women's roles from the domestic to the public sphere as a form of agency. The Abdi Mangungkung dance was selected because it contains complex sociocultural narratives regarding the struggle of Siti Rubiyah (BRAy Matah Ati) within the context of Javanese history and resistance to colonialism. Employing a qualitative case study approach, this research analyzes how gender identity, social status, and cultural background interact to shape the representation of empowered women. The findings indicate that the Abdi Mangungkung dance is not merely an aesthetic performance but serves as a symbol of the deconstruction of women's historical marginalization, positioning women as active political subjects. This research contributes to the interdisciplinary discussion on women's empowerment in the performing arts and its relevance to strengthening women's identity in today’s global society.